Greenhouse Gas Emission Disclosure and Company Size on Operational Performance - Zuhrotul Isnaini; Lukman Effendy; Wahidatul Husnaini (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the effect of Greenhouse gas emissions (GHG) and firm size on operation performance. The sample for this study was determined using purposive sampling with the criterion of manufacturing companies that disclose GRK. There were 37 sample companies for 3 years, namely 2019-2020. This study uses multiple regression using SPSS 26. The results of this study found that the disclosure of greenhouse gas emissions did not affect the operation performance but the size of the company affected the operation performance. The results of this study are expected to add to the literature and can be used by stakeholders who need this information as material for decision.